2022
DOI: 10.3390/ijms23052648
|View full text |Cite
|
Sign up to set email alerts
|

PSMD14 Targeting Triggers Paraptosis in Breast Cancer Cells by Inducing Proteasome Inhibition and Ca2+ Imbalance

Abstract: PSMD14, a subunit of the 19S regulatory particles of the 26S proteasome, was recently identified as a potential prognostic marker and therapeutic target in diverse human cancers. Here, we show that the silencing and pharmacological blockade of PSMD14 in MDA-MB 435S breast cancer cells induce paraptosis, a non-apoptotic cell death mode characterized by extensive vacuolation derived from the endoplasmic reticulum (ER) and mitochondria. The PSMD14 inhibitor, capzimin (CZM), inhibits proteasome activity but differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Therefore, targeting non-apoptotic forms of cell death, such as paraptosis, may have therapeutic benefits in apoptosis-defective cancer cells. Although the molecular basis of paraptosis remains to be clarified, it has been causatively linked to disruption of proteostasis, such as through inhibition of thiol proteostasis [11,[14][15][16][17] or proteasome [18][19][20][21]. We found that mono-inhibition of TrxR1 or proteasome does not induce a notable anticancer activity.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, targeting non-apoptotic forms of cell death, such as paraptosis, may have therapeutic benefits in apoptosis-defective cancer cells. Although the molecular basis of paraptosis remains to be clarified, it has been causatively linked to disruption of proteostasis, such as through inhibition of thiol proteostasis [11,[14][15][16][17] or proteasome [18][19][20][21]. We found that mono-inhibition of TrxR1 or proteasome does not induce a notable anticancer activity.…”
Section: Introductionmentioning
confidence: 79%
“…GSH also plays a crucial role in native disulfide bond formation within the ER [83], and GSHdependent proofreading occurs during mitochondrial disulfidemediated oxidative protein folding [84]. Proteostatic disruption, including impairment of protein thiol homeostasis [11,[14][15][16][17] and proteasomal inhibition [18][19][20][21], has been critically implicated in paraptosis. The vacuolization observed during paraptosis is believed to reflect the influx of water into the ER and mitochondria when osmotic pressure is increased by misfolded proteins accumulated within these organelles [11].…”
Section: Discussionmentioning
confidence: 99%
“…GSH also plays a crucial role in native disul de bond formation within the ER 68 , and GSH-dependent proofreading occurs during mitochondrial disul de-mediated oxidative protein folding 69 . Proteostatic disruption, including impairment of protein thiol homeostasis 11,14,15,16,17 and proteasomal inhibition 18,19,20,21 , has been critically implicated in paraptosis. The vacuolization observed during paraptosis is believed to re ect the in ux of water into the ER and mitochondria when osmotic pressure is increased by misfolded proteins accumulated within these organelles 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting non-apoptotic forms of cell death, such as paraptosis, may have therapeutic bene ts in apoptosis-defective cancer cells. Although the molecular basis of paraptosis remains to be clari ed, it has been causatively linked to disruption of proteostasis, such as through inhibition of thiol proteostasis 11,14,15,16,17 or proteasome 18,19,20,21 . We found that mono-inhibition of TrxR1 or proteasome does not induce anticancer activity; instead, inhibition of both TrxR1 and proteasome is required to induce paraptosis effectively.…”
Section: Introductionmentioning
confidence: 99%
“…PSMD14, also known as Rpn11 and POH1, is a subunit of the proteasomal 19S regulatory particle, which functions as a DUB [ 177 ]. PSMD14 overexpression has been reported to be tumorigenic and promote cancer progression through multiple mechanisms [ 177 , 178 , 179 , 180 , 181 ], such as stabilizing the alternative splicing factor PTBP1 to promote GC tumorigenesis [ 100 ].…”
Section: Jamms and Gcmentioning
confidence: 99%